Tornado-Induced and Straight-Line Wind Loads on a Low-Rise Building With Consideration of Internal Pressure - Roueche, David Brett; Prevatt, David O.; Haan, Frederick L. (Frontiers in Built Environment, 2020)
Tornado and straight-line wind events are often discussed and compared in terms of their intensity, e.g., maximum wind speed, however it is unclear to what extent tornado-induced and straight-line wind-induced wind loads are equivalent even for the same nominal intensity. This lack of understanding inhibits both tornado design philosophies and policies, and communication of tornado risk to the public. This study directly compares existing wind tunnel databases of tornado-induced and straight-line wind-induced pressures, for a similar building model, to evaluate to what extent the induced surface pressures on a typical building differ. The existing datasets used in the study are enhanced with a numerical internal pressure model to facilitate the comparison across a range of opening configurations that would be common in typical buildings. The analysis finds that differences are most pronounced in the overall distribution of pressures across the building surface, and in the magnitudes of pressures in regions of strong flow separation. However, overall the magnitudes of the peak tornado-induced pressures are reasonably similar to straight-line wind-induced pressures, with tornado-induced pressures on average 13% higher than equivalent straight-line wind-induced pressures. Ultimately, this study demonstrates a framework for such comparisons, while recognizing key sources of uncertainty and further research needs.